PENGARUH PEMBERIAN TERAPI BERMAIN TERHADAP PEMBELAJARAN MITIGASI BENCANA PADA ANAK AUTIS BERBASIS DISASTER NURSING COMPETENCY - Nur Indriasari, Fika; Widyarani, Linda; Daniyati Kusuma, Prima (MEDIA ILMU KESEHATAN, 2018)
Background: A powerful earthquake in Yogyakarta, causing major damage and many deaths. Children with autism are more vulnerable and have a greater risk of earthquake because they are have an intellectual, social and verbal disability to safe life independently. Objective: This research discussed the influence of play therapy on learning of disaster mitigation for children with autism. Method: This research used qualitative descriptive design and consider a sample of 30 children with autism in SLB N Pembina Yogyakarta. Play therapy in this research use drawing and coloring methods, also watching video about disaster preparedness. Results: Play therapy could effectively be applied as earthquake mitigation lesson to children with autism in SLB N Pembina Yogyakarta. Before interventions, there were 2 children (7%) able to draw on actions when an earthquake occurred, and increased to 19 children (63,33%) after interventions. Conclusion: Play therapy could be effectively applied to children with autism as earthquake disaster mitigation showed by an increase of children’s drawing and coloring ability on actions when an earthquake occurred for as much as 56,33%. Keyword: Children with autism, mitigation ability, play therapy